The Working Culture of Legal Aid Lawyers: Developing a 'Shared Orientation Model'. (October 2022) - Cooke, Emma
This paper critically explores the working culture of legal aid lawyers and develops a novel 'Shared Orientation' model to better understand contemporary legal aid work and its workers. Set within a context of changing professional identities, a shrinking industry and financial constraints, the paper draws on ethnographic and interview data conducted with a high-street firm, multiple courtrooms and a law centre. It examines the emerging relevance and applicability of this new conceptual lens, refocusing the gaze on working life in fissured legal workplaces. It is argued that the 'Shared Orientation' model upholds multiple functions. Firstly, it captures the cultural heterogeneity of the legal aid profession, across civil-criminal and solicitor-barrister remits alike. Secondly, the model functions as a form of cohesive coping mechanism in response to the changing professional identity of the legal aid lawyers. Moreover, the 'Shared Orientation' offers unity as a way of functioning in an otherwise fragmented profession through its preservation of working culture ideals.